Facile one-step synthesis of nitrogen-doped carbon sheets supported tungsten carbide nanoparticles electrocatalyst for hydrogen evolution reaction. (27th November 2020) - Su, Wei; Yan, Pengpeng; Wei, Xiaofeng; Zhu, Xuewei; Zhou, Qiongyu
Abstract: Exploring non-precious metal catalysts with high activity and stability to replace Pt-based materials is vital for electrochemical water splitting. In this work, a facile one-step method was put forward to synthesize WC/NC composite. Due to the couple effect of KCl/NaCl salt and dicyandiamide, pure WC phase was obtained at 900 °C. Meanwhile, KCl/NaCl salt eliminated the runaway pyrolysis expansion of glucose. Besides contributing to the special surface area, dicyandiamide as N source significantly alleviated W mass loss trigged by KCl/NaCl salt and ensured the appropriate WC content in WC/NC composite. As a HER electrocatalyst in acid media, WC/NC composite exhibits the small overpotential of 156 mV at a current density of 10 mA cm −2, the low Tafel slope of 64 mV dec −1, as well as the robust stability. This work offers a feasible option to fabricate low-cost and effective transition metal carbide electrocatalysts on a large-scale for hydrogen evolution reaction. Highlights: A facile one-step method was developed to synthesize WC/NC catalyst. KCl/NaCl salt can eliminate the runaway pyrolysis expansion of glucose. W mass loss can be significantly suppressed by dicyandiamide. Dicyandiamide contributes to improve the electrochemical active surface area. WC/NC catalyst shows high activity and remarkable stability for HER in acid media.